Spontaneous Regression of Plasmablastic Lymphoma in an Immunocompetent Patient: Case Report and Review of the Literature - Lee, Kee Tat; Misron, Nurul Akmar; Abdul Aziz, Norasmidar; Wong, Chin Hau; Liew, Hong Keng (Case Reports in Hematology, 2022)
Plasmablastic lymphoma (PBL) is a rare and highly aggressive type of lymphoma, which is commonly associated with human immunodeficiency virus (HIV) infection. Spontaneous regression of aggressive lymphomas is rare as they typically require administration of chemotherapy and radiotherapy for treatment. Here, we describe a case of a spontaneous regression of PBL after nasal biopsy and computed tomography (CT) guided biopsy of paravertebral mass in an immunocompetent patient. We postulate that the patient’s immune system may be activated as a result of the stress and physical trauma brought on by nasal and paravertebral mass biopsy. Our case highlights the rare phenomenon of spontaneous regression of lymphoma which needs to be further studied on to establish its underlying pathophysiology.